Upregulation of cadherin‐11 contributes to cholestatic liver fibrosis. Issue 2 (22nd March 2022) - Wu, Bo; Tian, Xinbei; Wang, Weipeng; Zhu, Jing; Lu, Ying; Du, Jun; Xiao, Yongtao
ABSTRACT: Importance: Cadherin‐11 (CDH11), a cell‐to‐cell adhesion molecule, is implicated in the fibrotic process of several organs. Biliary atresia (BA) is a common cholestatic liver disease featuring cholestasis and progressive liver fibrosis in children. Cholestatic liver fibrosis may progress to liver cirrhosis and lacks effective therapeutic strategies. Currently, the role of CDH11 in cholestatic liver fibrosis remains unclear. Objective: This study aimed to explore the functions of CDH11 in cholestatic liver fibrosis. Methods: The expression of CDH11 in BA livers was evaluated by database analysis and immunostaining. Seven BA liver samples were used for immunostaining. The wild type (Wt) and CDH11 knockout ( CDH11 –/– ) mice were subjected to bile duct ligation (BDL) to induce cholestatic liver fibrosis. The serum biochemical analysis, liver histology, and western blotting were used to assess the extent of liver injury and fibrosis as well as activation of transforming growth factor‐β (TGF‐β)/Smad pathway. The effect of CDH11 on the activation of hepatic stellate cell line LX‐2 cells was investigated. Results: Analysis of public RNA‐seq datasets showed that CDH11 expression levels were significantly increased in livers of BA, and CDH11 was correlated with liver fibrosis in BA. BDL‐induced liver injury and liver fibrosis were attenuated in CDH11 –/– mice compared to Wt mice. The protein expression levels of phosphorylated Smad2/3 were decreased in livers of CDH11 –/– BDL mice compared to Wt BDL mice. CDH11 knockdown inhibited the activation of LX‐2 cells. Interpretation: CDH11 plays an important role in cholestatic liver fibrosis and may represent a potential therapeutic target for cholestatic liver disease, such as BA. Abstract : When cholestatic liver injuries are caused, cadherin‐11 is upregulated in the livers. In cholestatic livers, cadherin‐11 activates the TGF‐β/Smad signaling pathway, promotes the activation of hepatic stellate cells, and contributes to cholestatic liver fibrosis. Cadherin‐11 may represent a potential therapeutic target for cholestatic liver diseases, such as biliary atresia.